Implementasi Kebijakan Pencegahan Covid-19 di Kota Padang - Arya Bayu Firdaus; Ramadhani Yusran (PUBLICNESS: Journal of Public Administration studies, 2022)
Covid-19 is a novel disease that is spread by viruses in the Corona virus family, most notably SARS-CoV-2, or Corona Virus.The main idea of this study is to ascertain the effectiveness of government interventions aimed at avoiding COVID-19.This study combines qualitative and descriptive methodologies.The investigation was conducted in Padang City, West Sumatra Province.Observation, interviewing, and documentation studies are all methods of data collection.Meanwhile, this research employs reduction of the data, display of data, and the conclusion making methodologies.This research findings indicate that the Padang City government's efforts to address community needs and resolve community problems, most notably through the issuance of Perwako policy No. 32 of 2020 in Padang City, demonstrate the government's commitment to resolving social problems and national non-natural disasters, particularly in the Padang city area.Thus, the government's efforts to avoid COVID-19 in connection with the Perwako policy are considered to be proceeding smoothly and successfully.